2019
DOI: 10.1158/1535-7163.mct-19-0261
|View full text |Cite
|
Sign up to set email alerts
|

Transgelin 2 Promotes Paclitaxel Resistance, Migration, and Invasion of Breast Cancer by Directly Interacting with PTEN and Activating PI3K/Akt/GSK-3β Pathway

Abstract: MDR and tumor migration and invasion are still the main obstacles to effective breast cancer chemotherapies. Transgelin 2 has recently been shown to induce drug resistance, tumor migration, and invasion. The aim of this study was to determine the biological functions of Transgelin 2 and the mechanism underlying how Transgelin 2 induces paclitaxel (PTX) resistance and the migration and invasion of breast cancer. We detected that the protein level of Transgelin 2 was significantly upregulated in breast cancer ti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Impediments to apoptosis, reducing drug accumulation, alterations in cell cycle and enhancement of the tumor energy supply are the main reasons for MDR. Increases in DNA repair capacity, checkpoint changes, the presence of CSCs in tumors, gene mutations (PTEN mutations or disappearance, mutations in the TP53 gene), changes in drug target separation and epithelial-mesenchymal transition are also related to MDR [133][134][135] . These mechanisms must be carefully discussed in the future.…”
Section: Prospective and Conclusionmentioning
confidence: 99%
“…Impediments to apoptosis, reducing drug accumulation, alterations in cell cycle and enhancement of the tumor energy supply are the main reasons for MDR. Increases in DNA repair capacity, checkpoint changes, the presence of CSCs in tumors, gene mutations (PTEN mutations or disappearance, mutations in the TP53 gene), changes in drug target separation and epithelial-mesenchymal transition are also related to MDR [133][134][135] . These mechanisms must be carefully discussed in the future.…”
Section: Prospective and Conclusionmentioning
confidence: 99%
“…Additionally, PRLR/Jak2/STAT5 is the main signaling pathway for activation in mammary gland, and PRLR-triggered pro-tumorigenic pathways in BC include the PI3K/AKT pathway [172]. As well, numerous studies have shown that IRS4, CDK12, SPC24, Mfng, Transgelin 2, STX3, SOX4, PAK4, TPX2, MEG3 and miR-21, -93, -106b, -130b, -214, -361-5p, -489, -511, -564 as well as lncRNA-HOTAIR and MALAT1 regulate tumorigenesis, proliferation, apoptosis, invasion, migration, paclitaxel resistance or anti-Her2 therapy (trastuzumab) resistance of BC cells through PI3K/AKT pathway [173][174][175][176][177][178][179][180][181][182][183][184][185][186][187][188][189][190][191]. And then, PI3K/AKT inhibitors have gained wide attentions, and a large number of clinical trials may have provided tremendous promises in the treatment of BC patients (shown in Tables 2 and 3).…”
Section: Nct02240212mentioning
confidence: 99%
“…For example, hypoxia-activated AKT led to overexpression of MRP1 in hepatocellular carcinoma 33 . Transgelin2 motivated AKT and enhanced MRP1 via GSK-3β-dependent pathways in breast cancer 34 . Aberrant expression of glucose transporter 1 enhanced phosphorylation of AKT and promoted Survivin expression, inducing chemoresistance of triplicate-negative breast cancer 35 .…”
Section: Discussionmentioning
confidence: 99%